Cumulative costs of severe traffic injuries in Finland: a 2-year retrospective observational study of 252 patients - Riuttanen, Antti; Karjalainen, Erkka; Jokihaara, Jarkko; Huttunen, Tuomas T.; Mattila, Ville M. (Scientific reports, 2024)
Road traffic injuries cause considerable financial strain on health care systems worldwide. We retrospectively analyzed injury-related costs of 252 severely injured (New Injury Severity Score, NISS ≥ 16) patients treated at Tampere University Hospital (TAUH) between 2013 and 2017, with 2-year follow-up. The costs were divided into direct treatment, indirect costs, and other costs. We analyzed various injury- and patient-related factors with costs. The total costs during the 2-year study period were 20 million euros. Median cost was 41,202 euros (Q1 23,409 euros, Q3 97,726 euros), ranging from 2,753 euros to 549,787 euros. The majority of costs (69.1%) were direct treatment costs, followed by indirect costs (28.4%). Other costs were small (5.4%). Treatment costs increased with the severity of the injury or when the injury affected the lower extremities or the face. Indirect costs were higher in working age patients and in patients with a higher level of education. The relative proportions of direct and indirect costs were constant regardless of the amount of the total costs. The largest share of costs was caused by a relatively small proportion of high-cost patients during the 1st year after injury. Combined, this makes planning of resource use challenging and calls for further studies to further identify factors for highest costs.